Calcitonin gene‐related peptide induces the histone H3 lysine 9 acetylation in astrocytes associated with neuroinflammation in rats with neuropathic pain. (16th August 2021) - Sun, Chenyan; An, Qi; Li, Ruidi; Chen, Shuhui; Gu, Xinpei; An, Shuhong; Wang, Zhaojin
Abstract: Aims: Calcitonin gene‐related peptide (CGRP) as a regulator of astrocyte activation may facilitate spinal nociceptive processing. Histone H3 lysine 9 acetylation (H3K9ac) is considered an important regulator of cytokine and chemokine gene expression after peripheral nerve injury. In this study, we explored the relationship between CGRP and H3K9ac in the activation of astrocytes, and elucidated the underlying mechanisms in the pathogenesis of chronic neuropathic pain. Methods: Astroglial cells (C6) were treated with CGRP and differentially enrichments of H3K9ac on gene promoters were examined using ChIP‐seq. A chronic constriction injury (CCI) rat model was used to evaluate the role of CGRP on astrocyte activation and H3K9ac signaling in CCI‐induced neuropathic pain. Specific inhibitors were employed to delineate the involved signaling. Results: Intrathecal injection of CGRP and CCI increased the number of astrocytes displaying H3K9ac in the spinal dorsal horn of rats. Treatment of CGRP was able to up‐regulate H3K9ac and glial fibrillary acidic protein (GFAP) expression in astroglial cells. ChIP‐seq data indicated that CGRP significantly altered H3K9ac enrichments on gene promoters in astroglial cells following CGRP treatment, including 151 gaining H3K9ac and 111 losing this mark, which mostly enriched in proliferation, autophagy, and macrophage chemotaxis processes. qRT‐PCR verified expressions of representative candidate genes (ATG12, ATG4C, CX3CR1, MMP28, MTMR14, HMOX1, RET) and RTCA verified astrocyte proliferation. Additionally, CGRP treatment increased the expression of H3K9ac, CX3CR1, and IL‐1β in the spinal dorsal horn. CGRP antagonist and HAT inhibitor attenuated mechanical and thermal hyperalgesia in CCI rats. Such analgesic effects were concurrently associated with the reduced levels of H3K9ac, CX3CR1, and IL‐1β in the spinal dorsal horn of CCI rats. Conclusion: Our findings highly indicate that CGRP is associated with the development of neuropathic pain through astrocytes‐mediated neuroinflammatory responses via H3K9ac in spinal dorsa horn following nerve injury. This study found that CGRP act on their astrocytic receptors and lead to H3K9 acetylation (H3K9ac), which are mainly associated with proliferation‐, autophagy‐, and inflammation‐related gene expression. The number of astrocytes with H3K9ac expression is increased after nerve injury. Inhibition of CGRP attenuates the development of neuropathic pain, which was accompanied by the suppression of H3K9ac, CX3CR1, and IL‐1β expression in CCI rats. Abstract : This study find that CGRP act on their astrocytic receptors and lead to H3K9 acetylation (H3K9ac), which are mainly associated with proliferation‐, autophagy‐ and inflammation‐related gene expression. The number of astrocytes with H3K9ac expression is increased after nerve injury. Inhibition of CGRP attenuates the development of neuropathic pain, which was accompanied by the suppression of H3K9ac, CX3CR1, IL‐1β expression in CCI rats.